PSYCHOLOGICAL ASPECTS OF OBJECTIVE ASSESSMENT: STUDENT PERCEPTION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
In education, assessment plays a central role in shaping both student learning outcomes and motivation. Among various assessment methods, objective assessment—often characterized by standardized tests, multiple-choice questions, and automated grading—aims to minimize bias and subjectivity. However, while these tools provide uniform criteria for evaluation, the psychological effects on students are multifaceted. Understanding how students perceive and respond to objective assessment is crucial for educators aiming to create an environment conducive to learning and development. This article delves into the psychological dimensions of objective assessment, exploring student perceptions, their impact on motivation and stress, and how objective methods can be optimized for better learning outcomes